Effective photodegradation of antibiotics by guest-host synergy between photosensitizer and bismuth vanadate: Underlying mechanism and toxicity assessment. (June 2023) - Tan, Meihong; Shi, Wanping; Wang, Haifeng; Di, Guanglan; Xie, Zhengxin; Fan, Shisuo; Tang, Jun; Dong, Fengshou
Abstract: The removal of antibiotics in wastewater has attracted increasing attention. Herein, a superior photosensitized photocatalytic system was developed with acetophenone (ACP) as the guest photosensitizer, bismuth vanadate (BiVO4 ) as the host catalyst and poly dimethyl diallyl ammonium chloride (PDDA) as the bridging complex, and used for the removal of sulfamerazine (SMR), sulfadiazine (SDZ) and sulfamethazine (SMZ) in water under simulated visible light (λ > 420 nm). The obtained ACP-PDDA-BiVO4 nanoplates attained a removal efficiency of 88.9%–98.2% for SMR, SDZ and SMZ after 60 min reaction and achieved kinetic rate constant approximately 10, 4.7 and 13 times of BiVO4, PDDA-BiVO4 and ACP-BiVO4, respectively, for SMZ degradation. In the guest-host photocatalytic system, ACP photosensitizer was found to have a great superiority in enhancing the light absorption, promoting the surface charge separation-transfer and efficient generation of holes (h + ) and superoxide radical ( · O 2 − ), greatly contributing to the photoactivity. The SMZ degradation pathways were proposed based on the identified degradation intermediates, involving three main pathways of rearrangement, desulfonation and oxidation. The toxicity of intermediates was evaluated and the results demonstrated that the overall toxicity was reduced compared with parent SMZ. This catalyst maintained 92% photocatalytic oxidation performance after five cyclic experiments and displayed a co-photodegradation ability to others antibiotics (e.g., roxithromycin, ciprofloxacin et al.) in effluent water. Therefore, this work provides a facile photosensitized strategy for developing guest-host photocatalysts, which enabling the simultaneous antibiotics removal and effectively reduce the ecological risks in wastewater. Graphical abstract: Image 1 Highlights: A guest-host photosensitized photocatalytic nanoplates was developed. The nanoplates showed superior degradation performance for the SMR, SDZ and SMZ. ACP photosensitizer greatly promoting the surface charge separation-transfer. The overall toxicity of intermediates was reduced compared with parent SMZ.